Proposing an Examen for Living the Ecology of Daily Life and Building a Culture of Care - Savino, Damien Marie (The Trumpeter)

(untitled) (Athabasca University Press, 2018)
This article examines a relatively unexplored aspect of integral ecology in Laudato Si’ called “the ecology of daily life” and considers how living a healthy ecology of daily life relates to the unique vocation of humans to care for creation. Specifically, what does the Pope intend by “the ecology of daily life”? What are some obstacles to living it? How can living the ecology of daily life help build a culture of care? Based upon the principles articulated in the encyclical, the article proposes an examen for assessing progress in living the ecology of daily life. This examen is applied to two case studies in order to discern a fruitful practice of the ecology of daily life. The case studies represent environmental situations that, while affected by larger scale industrial/commercial processes, are primarily driven by micro-scale decision-making and small daily actions of individuals and local communities. The first case study focuses on endocrine disrupting chemicals as an example of a polluted ecology of daily life, and the second highlights a zero waste initiative as an exemplar of an integral ecology of daily life. The article concludes with comments on lessons learned from the exercise of applying the examen to two concrete situations. This approach can help individuals and communities discern how to build a culture of care based upon the principles of the ecology of daily life as they are presented in Laudato Si’.